Cost-effectiveness of nivolumab plus gemcitabine-cisplatin as first-line treatment for advanced urothelial carcinoma in China and the United States - Xiang, Guiyuan; Huang, Yueyue; Gan, Lanlan; Wang, Linning; Ding, Yunqi; Wu, Yuanlin; Xing, Haiyan; Liu, Yao (Frontiers in Immunology, 2024)
Objective Nivolumab, recently proven in a phase 3 clinical trial (CheckMate 901) to enhance survival when combined with gemcitabine-cisplatin for advanced urothelial carcinoma. This study aimed to assess its cost-effectiveness against gemcitabine-cisplatin alone, from US and Chinese payers’ perspectives. Methods A partitioned survival model was established to assess the life-years, quality-adjusted life-years (QALYs), lifetime costs, and incremental cost-effectiveness ratios (ICERs) of nivolumab plus gemcitabine-cisplatin versus gemcitabine-cisplatin alone as first-line treatment for advanced urothelial carcinoma. Univariate, two-way, and probabilistic sensitivity analyses were conducted to assess the model’s robustness. Additionally, subgroup analyses were performed. Results Nivolumab plus gemcitabine-cisplatin and gemcitabine-cisplatin achieved survival benefits of 4.238 life-years and 2.979 life-years for patients with advanced urothelial carcinoma, respectively. Compared with gemcitabine-cisplatin, nivolumab plus gemcitabine-cisplatin resulted in ICERs of $116,856/QALY in the US and $51,997/QALY in China. The probabilities of achieving cost-effectiveness at the current willingness-to-pay thresholds were 77.5% in the US and 16.5% in China. Cost-effectiveness could be reached if the price of nivolumab were reduced to $920.87/100mg in China. Subgroup analyses indicated that the combination had the highest probability of cost-effectiveness in patients under 65 or with an Eastern Cooperative Oncology Group (ECOG) performance-status score of 0 in the US and China. Conclusion Nivolumab plus gemcitabine-cisplatin first-line treatment for advanced urothelial carcinoma results in longer life expectancy than gemcitabine-cisplatin, but is not cost-effective in China at current price. However, cost-effectiveness is likely to be achieved in most patient subgroups in the US.